Themes of Adult Learning and Development in Human Resource Development - Shari Peterson; Mary K. Cooper (Adult Education Research Conference, 1999)
This hermeneutic study explores the practices and philosophies of Adult Education and Human Resource Development, so that integrated communities of practice maybe created by understanding the ways in which adult education theory informs the field of HRD.